Predicting first-trimester outcome of embryos with cardiac activity in women with recurrent spontaneous abortion - Li, Huixian (J Int Med Res, 2020)
OBJECTIVE: This study was performed to evaluate the capability of routine clinical indicators to predict the early outcome of embryos with cardiac activity in women with recurrent spontaneous abortion (RSA). METHODS: A retrospective cohort study of pregnant women with a history of RSA in a Chinese tertiary hospital was performed using unadjusted and multivariable logistic regression. RESULTS: Of 789 pregnant women with RSA, 625 (79.21%) had ongoing pregnancy, whereas 164 (20.79%) developed abortion before 20 full weeks of gestational age even after embryonic heart motion was detected. The final model had an area under the curve of 0.81 (95% confidence interval, 0.78–0.84) with a sensitivity of 74.39%, a specificity of 76.00%, and a false-positive rate of 52.32% at a fixed detection rate of 90%. CONCLUSIONS: The combination of multiple routine clinical indicators was valuable in predicting the early outcome of embryos with cardiac activity in viable pregnancies with RSA. However, this model might result in a high false-positive rate with a fixed detection rate of 90%; other markers must be investigated to identify first-trimester RSA once positive embryonic heart motion is established.